Active case detection and treatment of malaria in pregnancy using LAMP technology (LAMPREG): a pragmatic randomised diagnostic outcomes trial—study protocol - Mekonnen Teferi; Claire Kamaliddin; Hiwot Tilahun; Rediet Fikru Gebresenbet; Zelalem Mekonnen Bekele; Banchamlak Tegegne; Delenasaw Yewhalaw; Abebe Genetu Bayih; Dylan R Pillai; Filmona Mekuria; Getaneh Alemu; Beka Raya; et al. (BMJ Open)
Introduction Malaria is one of the major public health problems in sub-Saharan Africa. It contributes significantly to maternal and fetal morbidity and mortality in affected countries. This study aims to evaluate the impact of enhanced case detection using molecular testing called loop-mediated isothermal amplification (LAMP) on birth outcomes in a prospective study design.Methods and analysis A pragmatic randomised diagnostic outcomes trial will be conducted in several health institutes in different Ethiopian regions. Women (n=2583) in their first and second trimesters of pregnancy will be included in the study and individually randomised to the standard of care or enhanced case detection arms, and followed until delivery. Enrolment will encompass the malaria peak transmission seasons. In the standard of care arm, a venous blood sample will be collected for malaria diagnosis only in symptomatic patients. In contrast, in the intervention arm, mothers will be tested by a commercially available Conformité Européene (CE)-approved LAMP malaria test, microscopy and rapid diagnostic test for malaria regardless of their symptoms at each antenatal care visit. The primary outcome of the study is to measure birth weight.Ethics and dissemination The study was approved by the following ethical research boards: Armauer Hansen Research Institute/ALERT Ethics Review Committee (FORM AF-10-015.1, Protocol number PO/05/20), the Ethiopia Ministry of Science and Higher Education National Research Ethics Review Committee (approval SRA/11.7/7115/20), the Ethiopia Food and Drug Administration (approval 02/25/33/I), UCalgary Conjoint Health Research Ethics Board (REB21-0234). The study results will be shared with the institutions and stakeholders such as the Ethiopia Ministry of Health, the Foundation for Innovative Diagnostics, WHO’s Multilateral initiative on Malaria - Tropical Diseases Research (TDR-MIM), Roll Back Malaria and the Malaria in Pregnancy Consortium. The study results will also be published in peer-reviewed journals and presented at international conferences.Trial registration number NCT03754322.